2003
DOI: 10.1063/1.1624475
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact density measurements of tantalum and rhenium in the liquid and undercooled states

Abstract: Electrostatic levitation together with multibeam heating and ultraviolet imaging overcame contamination, imaging, and sample position stability problems associated with handling of liquid tantalum and rhenium. Here, the density [ρ(T)] of these metals is reported in the superheated and undercooled states. Over the 2760–3580 K interval, the density of tantalum was measured as ρ(T)=1.50×104−0.41(T−Tm) kg m−3, where the melting temperature Tm, was 3290 K. For rhenium, the density was determined (2700–3810 K) as ρ(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…1a and 2a) [27]. Three focused beams (50 W each) of CO 2 lasers (10.6 µm emission) in a same plane, separated by 120 degrees, hit the specimen.…”
Section: Multi-beam Heating Geometry [26 27]mentioning
confidence: 99%
See 1 more Smart Citation
“…1a and 2a) [27]. Three focused beams (50 W each) of CO 2 lasers (10.6 µm emission) in a same plane, separated by 120 degrees, hit the specimen.…”
Section: Multi-beam Heating Geometry [26 27]mentioning
confidence: 99%
“…Here is presented a summary of the thermophysical property measurements (density, vapor pressure, surface tension, viscosity) of refractory materials above as well as below their melting points. [27,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] The density was determined by simultaneously recording the temperature and images of a non-rotating spherical sample illuminated from behind with a UV source. Upon closing the shutters of all lasers, the sample was cooled and the data could be obtained over a large temperature range.…”
Section: Thermophysical-property Measurementsmentioning
confidence: 99%
“…[2][3][4][5][6][7] To the knowledge of the present authors, very little work has been reported on ESL measurements of oxide materials 8,9) and levitation of multicomponent oxide systems has never been reported yet. In the present study, the measurements of the density a complex slag by the ESL method and similar measurements by the sessile drop method have been carried out and the results are compared.…”
Section: Introductionmentioning
confidence: 97%
“…The levitation mechanism is conceptually simple, despite the experimental complications of an active control system required to maintain a stationary sample position. 1,2 Although limited to noncontact methods, a wide variety of thermophysical properties have been measured in ESL experiments, including heat capacity and hemispherical emissivity, [3][4][5] phase transition temperatures, 4,6,7 density and thermal expansion, 5,8,9 viscosity and surface tension, 5,10 electrical conductivity, 11 and x-ray or neutron scattering structure factors. 12,13 To further expand the electrostatic levitation technique and enable the measurement of transport properties of liquids, the contribution from convective transport must be either negligible or precisely known.…”
Section: Introductionmentioning
confidence: 99%